7‐3: A Low‐Power and High‐Stable TFT Gate Driver With a Novel Bootstrap Scheme. Issue 1 (May 2017) - Ma, Yihua; Liao, Congwei; Xie, Ruibin; Zhao, Qiang; Zhang, Shengdong
Abstract : A novel bootstrap method is proposed, which can significantly reduce the clock feedthrough effect and the dynamic power consumption. An ESL a‐IGZO TFTs based gate driver using this technique is designed. It is shown that the ripple voltage and the power consumption of the proposed driver are only 22.9% and 23.86% of those of the earlier driver.